2023
DOI: 10.1037/ccp0000815
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance is calming and curing—The interplay between alliance and emotion regulation as predictors of outcome in Internet-based treatments for adolescent depression.

Abstract: Objective: Therapeutic alliance is one of the most stable predictors of outcome in psychotherapy, regardless of theoretical orientation. The alliance–outcome relationship in internet-based treatments has been investigated with mixed results. There is preliminary evidence that emotion regulation can work as a mediator for the alliance–outcome relationship. The present study aimed to investigate whether alliance predicted outcome session by session in two internet-based treatments for adolescent depression, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…We should be particularly mindful of the possible importance of the therapeutic alliance in explaining the differential effects of our two treatments on features of psychopathy and emotion dysregulation. Results of a study by Lindqvist et al (2023) supported the hypothesis that emotion regulation is a critical factor that mediates the relationship between working alliance and treatment outcome. A systematic review by Fahlgren et al (2020) examined research on the relationship between alliance and outcome in the treatment of highly aggressive individuals and those diagnosed with a disorder for which aggression is a primary symptom, including antisocial and borderline PDs.…”
Section: Discussionmentioning
confidence: 79%
“…We should be particularly mindful of the possible importance of the therapeutic alliance in explaining the differential effects of our two treatments on features of psychopathy and emotion dysregulation. Results of a study by Lindqvist et al (2023) supported the hypothesis that emotion regulation is a critical factor that mediates the relationship between working alliance and treatment outcome. A systematic review by Fahlgren et al (2020) examined research on the relationship between alliance and outcome in the treatment of highly aggressive individuals and those diagnosed with a disorder for which aggression is a primary symptom, including antisocial and borderline PDs.…”
Section: Discussionmentioning
confidence: 79%
“…In the treatment of both trauma and depression, the relationship between the client and therapist is of critical importance, with the common factors of therapeutic alliance, clinician empathy, and collaboration showing the largest effect sizes on outcomes across modalities (Wampold, 2015). Therapeutic alliance is especially well represented in the literature, with higher client ratings of alliance correlating to greater adherence, lower rates of dropout, and improved outcomes in the treatment of both depression and trauma (Howard et al, 2022; Keefe et al, 2022; Keller et al, 2010; Lindqvist et al, 2023; Murphy et al, 2022).…”
Section: Tpmentioning
confidence: 99%
“…Such studies might lead to increased understanding of how relationship factors are beneficial in therapy. Indeed, previous studies have found that the associations between relationship factors and outcome might be mediated by changes in specific processes that are often conceptualized as underlying components of psychopathology, such as changes in emotion regulation difficulties and specific cognitions (e.g., Hoffart et al, 2012; Lindqvist et al, 2023). This indicate that the healing power of the therapeutic relationship might occur through changing maladaptive functioning.…”
mentioning
confidence: 99%